THE ECLECTIC APPROACH IN TEACHING ENGLISH (Konferensiyalar | Conferences, 2024)
is study is to investigate the effectiveness of the eclectic approach in teaching English. It describes some challenges in teaching and propose the advantages of eclectic approach for teaching English as a second language.